DEVELOPMENT OF HOLISTIC-BASED SCIENCE LEARNING VIDEOS : AN EFFORT TO IMPROVE AFFECTIVE SKILLS OF MADRASAH IBTIDAIYAH STUDENTS - Juhji Juhji; Miftahul Jannah; Asep Saefurohman (UIN Sumatera Utara Medan, 2022)
There is a tendency to ignore students' affective skills from the science learning process in the classroom. Therefore, the purpose of this research is to develop a holistic science-based learning video in order to improve the affective skills of students. The research method used is the research and development of the ADDIE model. A total of 14 students involved themselves as subjects in a limited test. The results showed that the holistic-based learning video developed by the researcher was suitable for improving the affective skills of the fifth-grade students of Madrasah Ibtidaiyah. The media and materials expert validation test results showed that the percentages were 81 percent and 89 percent, respectively, in the very feasible category. The responses of teachers and students also show the same thing, which shows that the video is very suitable to be used to improve students' affective skills. This research recommends that students' affective skills can be improved through holistic science-based learning videos.